Generating Diverse Spinal Motor Neuron Subtypes from Human Pluripotent Stem Cells - Rickie Patani (Stem Cells International)
Resolving the mechanisms underlying human neuronal diversification remains a major challenge in developmental and applied neurobiology. Motor neurons (MNs) represent a diverse pool of neuronal subtypes exhibiting differential vulnerability in different human neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA). The ability to predictably manipulate MN subtype lineage restriction from human pluripotent stem cells (PSCs) will form the essential basis to establishing accurate, clinically relevant in vitro disease models. I first overview motor neuron developmental biology to provide some context for reviewing recent studies interrogating pathways that influence the generation of MN diversity. I conclude that motor neurogenesis from PSCs provides a powerful reductionist model system to gain insight into the developmental logic of MN subtype diversification and serves more broadly as a leading exemplar of potential strategies to resolve the molecular basis of neuronal subclass differentiation within the nervous system. These studies will in turn permit greater mechanistic understanding of differential MN subtype vulnerability using in vitro human disease models.